Search for the HH → bb¯ bb¯ process via vector-boson fusion production using proton-proton collisions at √s = 13 TeV with the ATLAS detector - Fiolhais, M. C. N. (2020)
A search for Higgs boson pair production via vector-boson fusion (VBF) in the b bb b nal state is carried out with the ATLAS experiment using 126 fb1 of protonproton collision data delivered at p s = 13 TeV by the Large Hadron Collider. This search is sensitive to VBF production of additional heavy bosons that may decay into Higgs boson pairs, and in a non-resonant topology it can constrain the quartic coupling between the Higgs bosons and vector bosons. No signi cant excess relative to the Standard Model expectation is observed, and limits on the production cross-section are set at the 95% con dence level for a heavy scalar resonance in the context of an extended Higgs sector, and for non-resonant Higgs boson pair production. Interpretation in terms of the coupling between a Higgs boson pair and two vector bosons is also provided: coupling values normalised to the Standard Model expectation of 2V < 0:76 and 2V > 2:90 are excluded at the 95% con dence level in data.